2022
DOI: 10.3390/biomedicines10071761
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding Is an Independent Prognostic Factor in Pancreatic Adenocarcinoma and It Positively Correlates with PD-L1 Expression on Tumor Cells

Abstract: Pancreatic adenocarcinoma is one of the leading causes of cancer-related death in developed countries. Only 15% of patients are candidates for radical surgery, and adequate prognostication may guide proper postsurgical management. We aimed to retrospectively assess the prognostic significance of the immunohistochemical expression of immune checkpoint receptors (PD-L1 and VISTA), markers of systemic inflammation, thrombosis in the tumor area, and the tumor budding in the group of 107 patients diagnosed with pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Subsequently, a full‐text review was performed, during which studies with inadequate data or cohort presentation, as well as those lacking full‐text availability, the inadequate study design was excluded. Ultimately, 57 studies met our inclusion criteria and were included in our systematic review and meta‐analysis 4,5,16–70 . Manual‐checking references to ensure comprehensives did not yield any additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a full‐text review was performed, during which studies with inadequate data or cohort presentation, as well as those lacking full‐text availability, the inadequate study design was excluded. Ultimately, 57 studies met our inclusion criteria and were included in our systematic review and meta‐analysis 4,5,16–70 . Manual‐checking references to ensure comprehensives did not yield any additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…reported that although VISTA expression in immune cells and endothelial cells did not show an association with patient survival, there was a significant correlation between high levels of VISTA expression in pancreatic tumor cells and improved overall survival (OS) ( 78 ). Better OS is associated with high expression of PD-L1 or VISTA on immune cells present in the TME of PDAC ( 91 ). In contrast, in a study by Blando et al., survival was found to have an inverse correlation with the expression of the VISTA gene ( 30 ).…”
Section: Discussionmentioning
confidence: 99%